RELACIÓN ENTRE LA AUSENCIA DE GUÍAS FUNCIONALES Y LOS TRASTORNOS TEMPOROMANDUBULARES EN ESTUDIANTES DE LA CARRERA DE ODONTOLOGÍA EN LA UNIVERSIDAD NACIONAL DE CHIMBORAZO - Haro Espinosa, Daniel Ramiro (2019)
This research is intended to identify the “Relationship between the absence of functional guides and temporomandibular disorders of students the Dental career from National University of Chimborazo” Like the incisors, the superior and inferior canines when entering into function both in centric occlusion and in protrusive movements and of bulging in laterality have great importance in determining the different chewing patents of each individual. Temporomandibular disorders are a global health problem, their origin is multifactorial, and these can be influenced by factors such as the absence of functional guides. To establish a percentage of how the types of temporomandibular disorders related to the absence of the functional guidelines are presented, using a cross-sectional methodology with a sample of 30 students. Medical and dental records and extra oral and intraoral examinations were performed to observe the presence or absence of canine and incisive guides in laterality, protrusion, opening and closing movements as a function of the temporomandibular joint, previous photographs were taken to have a record of each patient as well as the analysis of the temporomandibular joint. Therefore, from this study, we can conclude that the 59%(17) of the total sample had right canine guidance while 41%(12) had no canine guide on the right and that 72%(28) had no left hand canine guide, 28%(8) presented group function 35.1%(20) presented atrial noise 3.5%(2) opening and closing pain